Retrospective analysis of the sex chromosomal copy number variations in 186 fetuses using single nucleotide polymorphism arrays - Wang, Haiwei; Liang, Bin; Wang, Yan; Huang, Hailong; Lin, Na; Xu, Liangpu (Frontiers in Genetics, 2022)
Sex chromosomal abnormalities are associated with multiple defects. However, the types of sex chromosomal abnormalities during pregnancy in Fujian province, China, are not recorded. In this retrospective analysis, we showed the sex chromosomal abnormalities of 186 fetuses, including162 cases of X chromosomal abnormalities and 22 cases of Y chromosomal abnormalities in Fujian province. We detected 73 cases of Turner syndrome, 24 cases of triple X syndrome, 37 cases of Klinefelter syndrome and 14 cases of XYY syndrome. 67.3% fetuses with classic Turner syndrome were growth arrested. Moreover, we found 21 cases of mosaic Turner syndrome, 3 cases of mosaic Triple X syndrome, 2 cases of mosaic Klinefelter syndrome and 1 case of mosaic XYY syndrome. Furthermore, 37 cases of large scales of sex chromosomal deletions/duplications were detected, including 30 cases of X chromosomal deletions/duplications and 7 cases of Y chromosomal deletions/duplications. Parent-of-origins of five cases of sex chromosomal deletions/duplications were determined. One case was with de novo X chromosomal variations, while, the sex chromosomal deletions/duplications in other four cases were inherited from their parents. Overall, our results presented a detailed manifestation of sex chromosomal abnormalities of 186 fetuses in Fujian province and suggested the important roles of single nucleotide polymorphism (SNP) array analysis in the prenatal diagnosis of sex chromosomal abnormalities. Also, determining the parent-of-origins of the deletions/duplications was critical for the prenatal diagnosis of sex chromosomal abnormalities.